2008
DOI: 10.1097/ppo.0b013e31816a0f07
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Nausea and Vomiting

Abstract: Chemotherapy-induced nausea and vomiting (CINV) affects many cancer patients and has a great influence on quality of life. CINV involves coordination of several organs of the gastrointestinal tract, the peripheral and central nervous systems. Many neurotransmitters are involved in this process, and the predominant receptors are serotonin, neurokinin-1 and dopamine receptors. Risk factors for CINV include patient gender and age, past history of CINV, plus the emetogenicity and administration schedule of chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 41 publications
2
80
0
1
Order By: Relevance
“…Chemotherapy-induced nausea and vomiting (CINV) is the most common side effect of cancer patients treated with highly emetogenic chemotherapy (1) and has a significant effect on the patients' daily functioning and well-being (2). Poor control of acute CINV, which occurs within 24 h after chemotherapy, may be used as a predictor of delayed CINV (3).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapy-induced nausea and vomiting (CINV) is the most common side effect of cancer patients treated with highly emetogenic chemotherapy (1) and has a significant effect on the patients' daily functioning and well-being (2). Poor control of acute CINV, which occurs within 24 h after chemotherapy, may be used as a predictor of delayed CINV (3).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, patients with a history of high alcohol consumption have lower risk of CINV. 3,4 A study of breast cancer patients has recently become available, and analysis in those receiving cyclophosphamide with doxorubicin or epirubicin combination chemotherapy confirmed that younger age (,55 years), no or low alcohol intake (0-4 drinks per week) and a history of pregnancyrelated morning sickness are risk factors for CINV. 5 These findings were supported by another study based on other cancer patients who received cisplatin-based chemotherapy, 6 in which female gender was also identified as a risk factor.…”
Section: Patient-related Factorsmentioning
confidence: 99%
“…[3] Other side effects are alopecia, weakness, loss of weight, fever, peripheral neuropathy and other gastrointestinal side effects like Diarrhea, Loss of appetite, Anorexia, Vomiting, Constipation, Stomatitis, Burning sensation. [4,5] Expenses and associated side effects of anticancer drugs have provoked the research for drugs with minimum side effects and low in cost. [6] Plants have been used as an age old remedy for treatment of cancer.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 99%